EXAMINING THE LEVEL OF SAFETY AND SECURITY THROUGH THE PRISM OF VIOLENCE AND ABUSE AMONG WOMEN PRISONERS - Kostevska, Dragana (International Scientific Journal Vision, 2021)
To specifically define the term security, whether we are referring to a situation, place, individual, or process, we need to look at many aspects, link many concepts, analyze numerous studies and conduct a number of projects and researches and again it would be impossible to give a universal definition to define security as a term. On the other hand, security finds daily application even in the simplest interpersonal relationships. Starting from this position, we wanted to examine the level of safety and security through the prism of degree of vulnerability in the only female prison in the Republic of Northern Macedonia. For this purpose, we conducted research within a five-month project, which was implemented in the Idrizovo Penitentiary, specifically in the Women’s Department. It involved 52 women convicts. Namely, the results of our research confirmed that a large number of women were victims of violence. Although these are women who have committed a crime, however, the results confirm the thesis that a large percentage of them were victims before committing the crime. If we add to this various risk factors that have led to the previous state of victimization, such as education, economic status, lack of professional qualifications and competencies, addictions, place of residence, previous criminal record, we assume that (un) security and victimization only gain momentum.